A Review of the Components of Problematic Exercise in Psychometric Assessment Instruments - Sicilia, Álvaro; Alcaraz-Ibáñez, Manuel; Paterna, Adrian; Griffiths, Mark D. (Frontiers in Public Health, 2022)
Backgrounds The range of theoretical conceptualizations of problematic exercise in psychometric assessment instruments makes it difficult to identify the components that define this phenomenon. A better understanding of the underlying components of problematic exercise may contribute to progress toward providing scientific evidence that allows for deciding whether problematic exercise should be considered a substantive mental health disorder. The objective of the present review was to examine and compare, through a content analysis of their items, the components of problematic exercise in psychometric assessment instruments identified in a recent systematic review. Methods A total of 33 components of problematic exercise were identified in the 17 assessment instruments included in the present review. Results The results show that, despite the lack of consensus in the operational definition of their factors and the variety of ways of wording their items, the instruments reflect some common components that might indicate core criteria (i.e., salience, withdrawal, and mood modification) or candidate components (i.e., conflict, and continuance despite problems) of problematic exercise. However, other components of different nature were shown to be specific to some of the problematic exercise conceptualizations on which the assessment instruments are based. Conclusion In the interest of reaching a consensus that allows to advance in this research field, further studies are needed to resolve which components are inherently problematic.